Uji Sensitivitas Neisseria gonorrhoeae terhadap Beberapa Antibiotik Pada Wanita Penjaja Seks (WPS) di Lokalisasi Tanjung Elmo Kabupaten Jayapura - Hamid Hamid; Dirk Runtuboi; Lucky V. Waworuntu (Jurnal Biologi Papua, 2014)
The purpose of this research is to study the sensitivity of quinolon antibiotic group against  Neisseria gonorrhea. The bacteria which were found from endoservic vaginal from local sexual worker of Tanjung Elmo, Jayapura were isolated using neck duck sterile. This study was done on Health Laboratory of Jayapura from June to September 2013. The swab was planted on Thayer-Martin medium and incubated at 37 ºC for 2 x 24 hours. The grown colonies were sub-cultured to get the specific colonies. The bacterial identification is done by some rapid test including examination of grams, oxidation tests, biochemical tests andsensitivitytest. The result showed that there were six (6) specimen of 52 samples positively contained N. gonorrhea. The sensitivity test of quinolone group indicated that the levofloxacin, cefixime, ciprofoxacin, ofloxacin, azytromisin have the sensivity of 83.3%, 66.6%, 66.6%, 66.6% and  50% respectively.Key words: Neisseria gonorrhea, female commercial sex workers, antibiotics